Stratigraphic and taxonomic significance of siliceous microfossils collected from the Turiec Basin, Western Carpathians (Slovakia) - Ognjanova-Rumenova, Nadja Georgieva; Pipík, Radovan (Acta Botanica Croatica, 2015)
This study provides the first biostratigraphic data of siliceous microfossils from Turiec Basin, Slovakia. The fossil diatom flora consists of 42 species and varieties, belonged to 22 genera. The diatom assemblage studied from the Turiec Basin bears a strong resemblance to assemblages from non-marine diatomaceous sediment of Miocene age from Rüdenschwinden, a village of the eastern slope of the Hohe Rhön (Central Germany), non-marine sediments of the early Late Miocene from the village of Szilagy (South Hungary), as well as from Bes Konak Basin, Turkey. The investigated profile is generally dominated by Alveolophora jouseana. The similarities and differences within the taxonomy of certain species belonging to the genera Aulacoseira, Alveolophora and Miosira are discussed. The accompanying species are species of the genus Fragilaria Lyngbye sensu lato from class Fragilariophyceae. The most interesting taxa belong to the genus Staurosirella – S. grunowii, S. leptostauron, S. martyi. Among them are two very unusual taxa identified only to genus. Ecological data for the diatom taxa and the diatom frustules/ chrysophycean stomatocysts ratio are used in an attempt to reconstruct in detail the palaeoecological conditions at the time of sediment deposition.